Design and fabrication of nano biologically sensitive field-effect transistor (nano bio-FET) for bio-molecule detection - Foo, Kai Loong; Mohammad, Kashif; Uda, Hashim, Prof. Dr. (American Institute of Physics, 2012)
Link to publisher's homepage at http://proceedings.aip.org/